2021
DOI: 10.1080/21670811.2021.1942114
|View full text |Cite
|
Sign up to set email alerts
|

Sourcing Pandemic News: A Cross-National Computational Analysis of Mainstream Media Coverage of COVID-19 on Facebook, Twitter, and Instagram

Abstract: This article explores the uses of sources in coverage of the COVID-19 pandemic in social media posts of mainstream news organizations in Brazil, Chile, Germany, Mexico, Spain, the U.K., and the U.S. Based on computational content analysis, our study analyzes the sources and actors present in more than 940,000 posts on COVID-19 published in the 227 Facebook, Instagram, and Twitter accounts of 78 sampled news outlets between January 1 and December 31 of 2020, comparing their relative importance across countries,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 62 publications
3
23
0
5
Order By: Relevance
“…For example, Zunino (2019) examined sources in the digital media in Argentina, one of its results was that they are neither diverse nor plural. This conclusion is similar in Chile, Mellado et al (2021) found that the use of sources in Chile is associated with political elites, above the observable quota in other Latin American countries such as Mexico or Brazil.…”
Section: Gender's Sources: Who Supplies Firsthand Information?supporting
confidence: 64%
“…For example, Zunino (2019) examined sources in the digital media in Argentina, one of its results was that they are neither diverse nor plural. This conclusion is similar in Chile, Mellado et al (2021) found that the use of sources in Chile is associated with political elites, above the observable quota in other Latin American countries such as Mexico or Brazil.…”
Section: Gender's Sources: Who Supplies Firsthand Information?supporting
confidence: 64%
“…In an ongoing study of the soundtracks from Western news coverage of the pandemic at the first major sites of infection and quarantine, such as Wuhan (China), Tehran (Iran), and Milan (Italy), researchers have found that the distribution of sound, silence, and music differs regionally and nationally [ 27 ]. Meanwhile, mainstream news organizations’ social media posts of different countries maintain a strong elite orientation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent empirical research based on aggregated Facebook data, scholars have found strong correlations between social ties (i.e., social connectedness via Facebook friendship) and the regional spread of COVID-19 in the US as well as Italy (Bailey et al, 2020 ; Kuchler et al, 2020 ). Furthermore, Twitter and web news data have been used to predict COVID-19 outbreaks (Jahanbin and Rahmanian, 2020 ; Mellado et al, 2021 ). Given the local origin of a new virus and higher controllability of outbreaks at a local scale, transnational mobility is seen as responsible for the growing risks that infectious diseases constitute for an increasingly globalized world.…”
Section: State Of Researchmentioning
confidence: 99%